A typology of barriers and enablers of scientific evidence use in conservation practice - Walsh, Jessica C.; Dicks, Lynn V.; Raymond, Christopher M.; Sutherland, William J. (Journal of environmental management, 2019)
Over the last decade, there has been an increased focus (and pressure) in conservation practice globally towards evidence-based or evidence-informed decision making. Despite calls for increased use of scientific evidence, it often remains aspirational for many conservation organizations. Contributing to this is the lack of guidance on how to identify and classify the array of complex reasons limiting research use. In this study, we collated a comprehensive inventory of 230 factors that facilitate or limit the use of scientific evidence in conservation management decisions, through interviews with conservation practitioners in South Africa and UK and a review of the healthcare literature. We used the inventory, combined with concepts from knowledge exchange and research use theories, to construct a taxonomy that categorizes the barriers and enablers. We compared the similarities and differences between the taxonomies from the conservation and the healthcare fields, and highlighted the common barriers and enablers found within conservation organizations in the United Kingdom and South Africa. The most commonly mentioned barriers limiting the use of scientific evidence in our case studies were associated with the day-to-day decision-making processes of practitioners, and the organizational structures, management processes and resource constraints of conservation organizations. The key characteristics that facilitated the use of science in conservation decisions were associated with an organization's structure, decision-making processes and culture, along with practitioners' attitudes and the relationships between scientists and practitioners. This taxonomy and inventory of barriers and enablers can help researchers, practitioners and other conservation actors to identify aspects within their organizations and cross-institutional networks that limit research use – acting as a guide on how to strengthen the science-practice interface. •We developed a comprehensive taxonomy of barriers & enablers to research use.•230 factors limit or enable the use of scientific evidence in conservation practice.•Organization structure & decision-making processes are key barriers to evidence use.•Links between researchers & practitioners strengthen science-practice interfaces.•Conservation professionals can use this typology to improve evidence use.